PERKAWINAN CAMPURAN ANTAR ETNIK JAWA DENGAN ETNIK BATAK MANDAILING DI DESA SUKA MAJU KABUPATEN ROKAN HULU PROVINSI RIAU - Aseh Budiati; Syafrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Inter-ethnic marriages are a phenomenon that often occurs in Indonesia because Indonesia has a variety of cultures that it has. Each culture certainly has different customs, but inter-ethnic marriages still occur. This is the question of some circles who usually prefer to marry one ethnicity. The purpose of this study is to determine the background that affect inter-ethnic marriages, especially Ethnic Javanese with the Mandailing Batak ethnicity and to see the interactions that occur. The research location is in Suka Maju Village, Tambusai District, Rokan Hulu Regency, Riau Province. Researchers are interested in conducting research in Suka Maju Village because the village is a transmigrant village surrounded by several villages that have Batailing Mandailing ethnicities. Therefore did not rule out the possibility of inter-ethnic marriages in the village. In this study using the theory of rational choice put forward by Coleman and interaction theory. In analyzing the data the researcher used descriptive qualitative methods with data collection techniques through observation, interviews and documentation as well as the types of supporting data, namely primary data and secondary data. The results of this study reveal that there are several background that affect individuals in intermarriage between Javanese and Mandailing Bataks, namely social, economic, environmental, cultural,and personality. Next the researchers found that in the interaction of each pair there were no difficulties because they agreed to use Indonesian for their daily lives. Suka Maju Village is a village that has an open attitude towards other ethnicities so that Suka Maju Village experiences an acculturation process in interethnic marriages. Each actor learns his partner's culture without leaving his original culture. The close environment between Javanese and Mandailing Bataks led to amalgamation and acculturation.  Keywords: intermarriage, Javanese ethnic, Mandailing Batak ethnic.